Corridor with Minton tiles - Ghosh, Ayan (Jio Institute, 2023)
Often overlooked and under-appreciated in the detailing of BMC is the extensive use of Minton tiles for the flooring. These tiles were originally imported from Straffordshire, England. The Minton's were experts in ceramic design and a leading tile manufacturer in Victorian England. Their tiles were much sought after and were used in some of the iconic buildings of the nineteenth century, like the US Capitol and both houses of the British Parliament.